The Effect of Compensation & Workload on Job Satisfaction through Motivation (Case Study at PT Bluebird Group TBK) - Putri, Rr Fakhrani Ulfah Fairiko; Kasmir, Kasmir (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
This research seeks to examine the factors that impact job satisfaction, including Compensation, Workload, and Motivation. The population consists of 51 permanent employees at PT Bluebird Group Pool XX. The study involves 51 employees, using a saturated sampling method. The research method is quantitative with SEM-PLS. The results showed that: 1) Compensation positively influences Motivation, 2) Compensation does not affect Job Satisfaction directly, 3) Compensation positively influences job satisfaction by enhancing motivation, 4) Workload does not affect Motivation, 5) Workload does not affect Job Satisfaction directly, 6) Workload does not affect Job Satisfaction through Motivation, 7) Motivation greatly influences job satisfaction in a positive way.